Shoot and root growth of two tropical grasses, Brachiaria ruziziensis and B. dictyoneura, as influenced by aluminium toxicity and phosphorus deficiency in a sandy loam oxisol of the eastern plains of Colombia - Hausller, K; Rao, Idupulapati M.; Schultze-Kraft, Rainer; Marschner, H (2006)
Phosphorus (P) deficiency and aluminium (Al) toxicity are widespread in Oxisols of the tropical savannas of eastern Colombia. A field experiment was conducted to determine the effect of Al toxicity and P deficiency on plant growth and nutrient uptake of two Brachiaria species. To examine the influence of nutrient supply and lime on root and shoot growth, two levels of fertiliser application (low and high) were superimposed on the control, lime and gypsum treatments. Results from this field study showed that growth limitations of B. ruziziensis and B. dictyoneura (syn. B. humidicola) did not result from either P deficiency or Al toxicity. B. ruziziensis, despite lower root length, produced under the experimental conditions more shoot dry matter than B. dictyoneura with similar or greater P and Ca concentrations. Therefore, efficiency of Ca and/ or P uptake per unit root length was greater in B. ruziziensis than in B. dictyoneura. This ability of B. ruziziensis may contribute to its rapid establishment during the first year of pasture growth. Further studies are warranted to verify the apparent growth responses of these grasses to application of Ca on these soils.